NAMA-NAMA SURGA DALAM AL QUR'AN DAN EFEK MAKNANYA - Khairul Fuadi (Universitas Islam Negeri Sumatera Utara Medan, 2025)
Good language is when the intended meaning can be conveyed by the words and sentences spoken. In addition, the choice of appropriate words is a key consideration in speaking. The words spoken should not be unfamiliar to the listener so that they are easy to understand. When conveying a message, it is best to use concise language that represents the intended meaning. When describing the nature of heaven, which is intangible, it is necessary to use language that is precise and capable of depicting heaven and all its attributes as if they were real. One example of such descriptions can be found in the names that refer to the meaning of heaven itself, such as jannah, dar maqamah, dar as salam, ar rahmah, dar an naim, and firdaus. Thus, anyone who hears these names can easily grasp and visualize them, making them worthy of striving for in this world. This paper will explore the messages and meanings contained in several names of paradise found in the Qur'an. Beyond their names, these terms also carry specific attributes that represent particular conditions. The method used is qualitative descriptive. Through this approach, it becomes evident how the language of the Quran seeks to bring the meaning of paradise closer to all humanity, even though it was initially addressed to the Arab people using their language (Arabic) to ensure ease of understanding.